(untitled) (Journal of the College of Languages (JCL), 2025)
Sam Shepard (1943-2017) was an acclaimed American playwright renowned for his exploration of familial themes. His works often examine the complexities and dysfunctions of family life, making him an important figure in modern theatre. Buried Child (1978), one of his most significant plays, won the Pulitzer Prize for Drama in 1979. The play stands out for its dark, surreal portrayal of the family narrative, setting it apart from more conventional realistic family dramas. The disintegration of the family depicted in Buried Child serves as an example for broader societal issues, emphasising the family’s crucial role as the foundation of society. This study aims to analyse the psychological aspects of familial disintegration in Buried Child, focusing on the reasons behind the family’s breakdown and its psychological impact on its individual members. By applying Murray Bowen’s Family Systems Theory and Sigmund Freud’s concepts of remembering, repeating, and working-through, the study provides a comprehensive understanding of the characters’ dysfunctional behaviours. The research highlights the importance of addressing familial issues, as they influence societal health. Through this analysis, this study stresses the cyclical and multigenerational nature of trauma and the potential for psychological recovery.